Who's Watching the Kids? - Donna Davis (EDIS)
FAR0306, a 2-page transcript of the Family Album Radio Program broadcast by Donna Davis, describes a study by the U.S. Census providing statistics on types of childcare arrangements families are making for preschoolers. Published by the UF Department of Family Youth and Community Sciences, March 2009.